1986
DOI: 10.1677/joe.0.1100251
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of blood oxytocin levels during suckling and parturition in the rat

Abstract: A detailed secretory profile of oxytocin during suckling and parturition was determined in unanaesthetized freely moving rats. Ten pups were reunited with their mothers after 12-15 h of separation. Unless the milk-ejection reflex occurred, there was no difference in serum oxytocin levels before separation and during the suckling of either four or five, or nine or ten pups. Serum oxytocin levels increased abruptly by 50.1 +/- 4.2 (S.E.M.) pmol/l (n = 9) at milk ejection, and declined rapidly with a half-life of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
1
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 8 publications
(17 reference statements)
9
77
1
1
Order By: Relevance
“…However, in these previous studies, only high concentrations of OT (Ͼ10 Ϫ10 M) were used. Circulating concentrations of OT in either the pregnant or nonpregnant state are less than 10 Ϫ10 M in both rat (21) and human (16,44). In our studies, there was no vasorelaxant response at any concentration as low as 10 Ϫ14 M. In other studies (data not shown), we measured no effect of OT with concentrations as low as 10 Ϫ25 M. Several in vitro studies have provided support for a possible direct vasorelaxation response to OT.…”
Section: Discussionsupporting
confidence: 52%
“…However, in these previous studies, only high concentrations of OT (Ͼ10 Ϫ10 M) were used. Circulating concentrations of OT in either the pregnant or nonpregnant state are less than 10 Ϫ10 M in both rat (21) and human (16,44). In our studies, there was no vasorelaxant response at any concentration as low as 10 Ϫ14 M. In other studies (data not shown), we measured no effect of OT with concentrations as low as 10 Ϫ25 M. Several in vitro studies have provided support for a possible direct vasorelaxation response to OT.…”
Section: Discussionsupporting
confidence: 52%
“…56: [336][337][338][339][340] 2010) xytocin (OT) is synthesized in the cell body of the OT cell in the hypothalamic paraventricular (PVN) and supraoptic nuclei (SON) and released into blood circulation from axon terminals in the neurohypophysis. Various kinds of physiological stimuli such as parturition, lactation, osmotic stimulus and stress are known to stimulate OT secretion [1][2][3][4]. In lactating rats, OT is released intermittently as a result of periodic and synchronized activation of OT cells distributed in both sides of the hypothalamus, whereas pups suck nipples continuously [5].…”
mentioning
confidence: 99%
“…Oxytocin was first recognised for its roles in female physiology including the induction of labour and milk ejection, roles that are evidenced by increasing oxytocin levels during lactation and labour (18). Additionally, oxytocin is the strongest uterogenic substance known to man and its agonists and antagonists have been used clinically to induce labour or halt premature labour, respectively (1).…”
Section: Classical Actions Of Oxytocinmentioning
confidence: 99%